Produção de hidrogênio a partir da manipueira em reator anaeróbio de leito fluidificado: efeito do pH - Cardoso, Pedro Herlleyson Gonçalves (2013)
The pH is an important parameter in anaerobic reactors, may influence the rate of hydrogen production and inhibit the action of microorganisms hidrogenotróficos, it may affect the activity of hydrogenase as well as the route of metabolism. In this context, the present research aimed to study the best operating condition in relation to the pH factor in Anaerobic Fluidized Bed Reactor (RALF) for enhanced biological production of hydrogen from wastewater processing cassava (manipueira) plus supplements. The reactor used in laboratory scale possessed height of 190 cm and total volume 4192 cm3 net volume used was 2.7 L. It was used as support material for microbial adhesion, expanded clay having a diameter of 2.8 to 3.35 mm. For starting the reactor was used as the inoculum, an anaerobic lagoon sludge that was liquid swine waste, it has undergone a heat treatment so that there was a selection of microorganisms, resulting mainly in anaerobic hidrogenotróficos . It was used for room temperature operation of the reactor (25 to 30°C), and the hydraulic retention time (HRT) was applied 2 h. For substrate (cassava), took it a Chemical Oxygen Demand (COD) theoretical initial 4000 mg.L- 1. For this study we evaluated different pH values in the range 4.0 to 5.3 . In this sense, according to the results obtained can be said that the experiment was effective for biohydrogen production from cassava in RALF, observing an optimum pH of 4.9 with a production volume checked 0,31 L/h/L and 3.5 mol H2/mol yield glucose, a conversion rate of hydrogen in cassava 88%. The route of butyric acid fermentation is the most prevalent in this pH value. The percentages of metabolites soluble in this pH were: 4% acetic acid, 54% butyric acid, 4% propionic acid, 22% caproic acid and 16% ethanol.